2006
DOI: 10.1007/s10832-006-5180-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mn-doping on TSDC and degradation of BaTiO3

Abstract: The effects of Mn-doping on TSDC (Thermally Stimulated Depolarization Current) and electrical degradation of BaTiO 3 have been investigated. TSDCs of undoped BaTiO 3 and Ba(Ti 1−x Mn x )O 3−δ exhibited the three sharp TSDC peaks around phase transition temperatures. TSDC of Ba(Ti 0.995 Mg 0.005 )O 2.995 increased gradually from 50 • C and this anomalous depolarization current kept going up well above the Curie temperature (∼130 • C). TSDCs of un-doped BaTiO 3 and Ba(Ti 0.995 Mn 0.005 )O 3−δ decreased in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…33 In contrast to permittivity measurements, the TSDC method 31,32,[34][35][36] is able to detect depolarization directly by measuring resulting currents.…”
mentioning
confidence: 99%
“…33 In contrast to permittivity measurements, the TSDC method 31,32,[34][35][36] is able to detect depolarization directly by measuring resulting currents.…”
mentioning
confidence: 99%
“…Meanwhile, the activation energy values of peak B are in the range of 0.64-0.76 eV and the average value is 0.71 eV. According to the movement of relaxation peaks and the activation energy value, it can be concluded that the relaxation peak B should be generated by oxygen vacancies (V O ) [16][17][18][19][20][21][22]. By comparing the activation energies of peak A and peak B, it can be concluded that peak A shows the higher value than peak B.…”
Section: Resultsmentioning
confidence: 99%
“…10b that the V O relaxation shows a long relaxation time in the range of 160-930 ls and an increase tendency with TSDC peak density, which is correlated with the migration of the polarized oxygen vacancies in dielectrics. The oxygen vacancies are depleted in the anodic region and piled-up in the cathodic region after polarization [16][17][18][19][20][21][22]. Under the suitable polarization conditions, some oxygen vacancies can migrate across the grain boundaries into adjacent grains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations